Program Injeksi Vitamin B-Kompleks pada Ternak Sapi di Desa Bulo-bulo, Kabupaten Bulukumba, Sulawesi Selatan - Sri Wahyuni; Sri Utami; Sri Lestari; Tutik Lusyta Aulyani; Soraya Faradila; Nur Rahmah Razak (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Cattle farming in Bulo-bulo Village has been practiced for generations. Although it is still a sideline activity, it is managed in a traditional and extensive manner. Farmers in this village need guidance in terms of cattle rearing and management, because one of the main obstacles faced is farm management that needs more attention so that their cows can grow optimally and healthily. One solution that can be implemented to overcome this problem is to provide nutrient-rich feed and add the necessary mineral and vitamin intake. The purpose of this activity is to increase the knowledge of farmers about cattle health maintenance patterns and the importance of providing vitamin B complex to cattle. The target group of this program is the Multi Agro cattle group, which consists of 20 members. Community serviceCattle farming in Bulo-bulo Village has been practiced for generations. Although it is still a sideline activity, it is managed in a traditional and extensive manner. Farmers in this village need guidance in terms of cattle rearing and management, because one of the main obstacles faced is farm management that needs more attention so that their cows can grow optimally and healthily. One solution that can be implemented to overcome this problem is to provide nutrient-rich feed and add the necessary mineral and vitamin intake. The purpose of this activity is to increase the knowledge of farmers about cattle health maintenance patterns and the importance of providing vitamin B complex to cattle. The target group of this program is the Multi Agro cattle group, which consists of 20 members. Community service activities are carried out with a variety of diverse methods, including: 1) Counseling on cattle health management; 2) Distribution of materials in pamphlet format; 3) Implementation of comprehensive cattle health checks; and 4) Injection of vitamin B complex in cattle. The whole series of community service activities went well and were enthusiastically received by local farmers. The delivery of material on the symptoms of vitamin deficiency in cattle, as well as the benefits and content of vitamin B complex, was enthusiastically followed by Multi Agro farmers and cattle groups. The vitamin B complex injection process was carried out on 30 cattle by directly visiting farmers' cages, including those in the garden or in the field. In addition, it is recommended that disease prevention is carried out through efforts to maintain cleanliness, ensure good sanitation, and provide vitamins and dewormers regularly. activities are carried out with a variety of diverse methods, including: 1) Counseling on cattle health management; 2) Distribution of materials in pamphlet format; 3) Implementation of comprehensive cattle health checks; and 4) Injection of vitamin B complex in cattle. The whole series of community service activities went well and were enthusiastically received by local farmers. The delivery of material on the symptoms of vitamin deficiency in cattle, as well as the benefits and content of vitamin B complex, was enthusiastically followed by Multi Agro farmers and cattle groups. The vitamin B complex injection process was carried out on 30 cattle by directly visiting farmers' cages, including those in the garden or in the field. In addition, it is recommended that disease prevention is carried out through efforts to maintain cleanliness, ensure good sanitation, and provide vitamins and dewormers regularly.